TOWARDS A CASHLESS SOCIETY IN INDONESIA: THE IMPACT ON ECONOMIC GROWTH AND INTEREST RATE - Jaka Aminata; Gabrielle Elberta Sjarif (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2020)
Cashless payment is created as a form of further innovation in a more efficient financial system that will bring a country into the era of a cashless society, so its presence is expected to increase economic growth and not change the effectiveness of monetary policy implementation. This study aims to find out whether cashless payment instruments affect economic growth and interest rate, as one of the monetary policy instruments in Indonesia. Cashless payments in this study consists of credit cards, debit/ATM cards, and electronic money. This study uses secondary data obtained from Bank Indonesia Payment System Statistics and the Central Bureau of Statistics, with time-series data from 2013-2019. The analytical tool used in estimating the regression model in this study is multiple linear regression analysis with 2 (two) regression models. The results showed that debit card and electronic money transaction have a significant positive effect on economic growth, credit card transactions have a significant positive effect on interest rate and debit card transactions have a negative significant effect on interest rate. While simultaneously, the cashless payment instruments significantly affect the economic growth and interest rate in Indonesia. The use of cashless payments needs to be continuously increased and encouraged so that it can be used more widely in the community, so it can continue to increase economic growth and eficiency.